Beneficial effects of bacterial agent/bentonite on nitrogen transformation and microbial community dynamics during aerobic composting of pig manure. (February 2020) - Guo, Honghong; Gu, Jie; Wang, Xiaojuan; Nasir, Mubasher; Yu, Jing; Lei, Liusheng; Wang, Jia; Zhao, Wenya; Dai, Xiaoxia
Graphical abstract: Highlights: Bacterial agent and bentonite can effectively reduce NH3 and N2 O emissions. Additives enhanced nitrification and denitrification processes in the compost. Bacterial agents promote ammonia oxidation process to reduce NH3 emissions. Bentonite affected denitrification process dominated by nirS and nirK genes. Proteobacteria most important denitrifying microorganisms. Abstract: This study investigated the effects of adding a bacterial agent (B) and bentonite (BT) on nitrogen transformation, nitrogen functional genes, and the microbial community dynamics during the aerobic composting of pig manure, as well as their contributions to NH3 and N2 O emissions. Treatments B, BT, and BT + B reduced the NH3 emissions by 31.34%, 18.82%, and 23.67%, respectively, and the N2 O emissions by 53.16%, 72.56%, and 63.41%. N2 O and NH3 emissions were strongly related to the functional genes. Adding bacterial agent promoted the ammonia oxidation process to reduce NH3 emissions, whereas the influence of bentonite on nitrogen conversion was mostly related to nirS and nirK in denitrification processes. Nitrification and denitrification were dominated by different functional microorganisms in various stages of composting, where Proteobacteria comprised the most important denitrifying microorganisms. Thus, the additives reduced NH3 and N2 O emissions by regulating nitrification and denitrification processes, and adding both was highly advantageous.